Intelligent resource allocation for joint radar-communication - Lee, Joash (Nanyang Technological University, 2022)
Autonomous vehicles (AVs) produce high data rates of sensory information from sensing systems. In a cooperative driving setting, efficient sharing and processing of this sensory information has the potential to achieve collective sensor fusion, among other advanced functionalities that can enhance safe and efficient mobility. For such sharing to occur, high data-rate communication becomes essential. Unfortunately, the forthcoming proliferation of faster mmWave communication networks has raised concerns on interference with automotive radar sensors, which has led to a body of research on Joint Radar-Communication (JRC). Current strategies for JRC often rely on specialised hardware, prior knowledge of the system model, and entail diminished capability in either radar or communication functions.